Degrading Surround Circles for Image Inpainting - Dhannoon, Ban N; Mahmoud, Rasha S (Al-Nahrain Journal of Science, 2018)
Image inpaintingrefers to the process of reconstructing lost part ofimages based on the background information. i.e., image Inpainting fills the missing or damaged region in an image utilizing spatialinformation of its neighboring region. Inpainting algorithm have numerous applications. Applications range from the reconstruction of missing blocks introduced by packet loss during wireless transmission, removing of impairments, such as cracks, scratches, and dirt, in scanned photographs and digitized artwork images, to removal of image objects such as logos, stamped dates, text, persons, and special effects on the scene. The main goal of the Inpainting algorithm is to modify the damaged region in animage in such a way that the inpainted region is undetectable to the ordinary observers who are not familiar with the original image. This paper proposes an automatic approach for image inpainting using special method that depend on inpainting degrading closed circles around the mask in the inpainting process to improve the quality of the results. The results show that our method is more efficient when compared with genetic - based image inpainting and particle swarm optimization based image inpainting based on subjective criteria.